Sugar infusion into trees: A novel method to study tree carbon relations and its regulations - Zhang, Yan-Li; Yang, Yue; Saurer, Matthias; Schaub, Marcus; Gessler, Arthur; Lehmann, Marco M.; Rigling, Andreas; Walser, Marco; Stierli, Beat; Hajjar, Noureddine; Christen, Daniel; Li, Mai-He (Frontiers in Plant Science, 2023)
Many carbon-related physiological questions in plants such as carbon (C) limitation or starvation have not yet been resolved thoroughly due to the lack of experimental methodology. As a first step towards resolving these problems, we conducted infusion experiments with bonsai trees (Ficus macrocarpa) and young maple trees (Acer pseudoplatanus) in the greenhouse, and with adult Scots pine trees (Pinus sylvestris) in the field, that were “fed” 13C-labelled glucose either through the phloem or the xylem. We then traced the 13C-signal in plant organic matter and respiration to qualitatively test whether trees can take up and metabolize exogenous sugars infused. Ten weeks after infusion started, xylem but not phloem infusion significantly increased the δ13C values in both aboveground and belowground tissues of the bonsai trees in the greenhouse, whereas xylem infusion significantly increased xylem δ13C values and phloem infusion significantly increased phloem δ13C values of the adult pines in the field experiment, compared to the corresponding controls. The respiration measurement experiment with young maple trees showed significant increased δ13C-values in shoot respired CO2 at the time of four weeks after xylem infusion started. Our results clearly indicated that trees do translocate and metabolize exogenous sugars, and because the phloem layer is too thin, and thus xylem infusion can be better operated than phloem infusion. This tree infusion method developed here opens new avenues and has great potential to be used for research on the whole plant C balance and its regulation in response to environmental factors and extreme stress conditions.